Fire control and prevention in metallic mining operations - Ortiz Sánchez, Oswaldo (2009)
Accesible and non accesible underground fires in metal mines may be generated but they are not so frequent as in coal mines. However, metal mine fires generally develop more extensively causing greater losses but with few deaths as compared with coal mine fires. There are many causes of fires in mining operations but those fires in unstable pyrites are more dangenous because of the rapid fine graned sulphyde oxidation in contac with oxigen in air or water. Fires in underground mines may be controlled by flooding of the affected area, suffocation and filling of the area by mud or tailings, this last being the efective way of fire fighting particularly in fires of large extension. Effective ways of fire prevention consist of preventing subsidence of the mined area by appropriate election of the mining method, no use of inflammable materials either as excavation support or insulating barrier, break material by blasting only in quantities that can be transported before high temperatures develop in the broken material, never use pyrite contained waste as filling of mined areas, and so on. The study presents a brief description of a mined area set on fire by spontaneus ignition of pyrite and other sulphydes. Also it presents the personnel organization and the plan proper to figth the fire. It estimates the level of direct and indirect costs of fire control in an underground mine.